ANALGOSEDATION OF NEWBORNS IN THE INTENSIVE CARE UNIT. HOW TO DEAL WITH PAIN SYNDROME - V.I. Pokhylko; D.A. Shkurupii; N.N. Adamchuk; Yu.I. Cherniavska; O.Yu. Boduliev (Bukovynian State Medical University, 2020)
Introduction. The issue of pain in newborns is becoming increasingly relevant, especially for children in intensive care units. Untreated pain reduces the response to treatment of underlying disease, the deterioration of nursing results, the formation of chronic pain and asthenia in the late periods. Aim. To conduct a comparative analysis of the effectiveness of pain therapy methods in newborns treated in the Anesthesiology and Intensive Care Department. Materials and Methods. A cohort prospective study was conducted, which included 20 full-term infants with pain after long-term surgery for congenital intestinal obstruction. Significantly, the children did not differ in sex, weight, did not have enteric insufficiency and severe comorbidities. Children were divided into two groups depending on the method of anesthesia. Group I (n = 10) - newborns who underwent analgesia by administering morphine intravenously. Group II (n = 10) - newborns to whom morphine was administered enterally in combination with intravenous administration of paracetamol for breakthrough pain. In order to determine the effectiveness of analgesic therapy in the conditions of ICU, we used the checklist for monitoring pain in newborns that we developed. Results. The results of the study show that after intravenous administration of morphine, a sufficient level of analgesia was immediately achieved, whereas the full effect after enteral administration was achieved only on the second day, and there was a need for additional analgesia with paracetamol. However, children who received a tablet in the form of morphine had significantly fewer hemodynamic complications and did not need long-term respiratory support. In addition, in children receiving the intravenous form of morphine, severe withdrawal symptoms were observed on the 7th day of the postoperative period, and newborns required analgesia with paracetamol, while oral administration of glucose during manipulations was sufficient for children of group II. The duration of stay in ICU is significantly shorter in children of group II, which also indicates a better tolerance of intestinal forms of morphine. Our pain monitoring checklist allows you to additionally conduct effective pain diagnostics, evaluate the dynamics of pain, and timely adjust pain therapy. Conclusions. Early diagnosis of pain syndrome is necessary for timely prescription of effective analgesic therapy. The use of tablet morphine in newborns with surgical pathology without enteric insufficiency has fewer complications and has better tolerance. Further studies are needed on the use of enteric forms of morphine in newborns with non-surgical pathology.